Identification of candidate genes associating with soybean cyst nematode in soybean (Glycine max L.) using BSA-seq - Haibo Hu; Liuxi Yi; Depeng Wu; Litong Zhang; Xuechao Zhou; Yang Wu; Huimin Shi; Yunshan Wei; Jianhua Hou (PeerJ)
Soybean cyst nematode disease represents the major soil-borne disease of soybean. Identifying disease-resistant genes in soybean has a substantial impact on breeding of disease-resistant crops and genetic improvement. The present work created the F2 population with the disease-resistant line H-10 and disease-susceptible line Chidou4. 30 respective F2disease-resistant and disease-susceptible individuals for forming two DNA pools for whole-genome re-sequencing were selected. As a result, a total of 11,522,230 single nucleotide polymorphism (SNPs) markers from these two parental lines and two mixed pools were obtained. Accordng to SNP-index based association analysis, there were altogether 741 genes out of 99% confidence interval, which were mainly enriched into regions of 38,524,128∼39,849,988 bp with a total length of 1.33 Mb contain 111 genes on chromosome 2, 27,821,012∼29,612,574 bp with a total length of 1.79 Mb contain 92 genes on chromosome 3, 308∼348,214 bp with a total of length 0.35 Mb contain 34 genes on chromosome 10, and 53,867,581∼58,017, 852 bp with a total length of 4.15 Mb contain 504 genes on chromosome 18. Bulk segregant analysis in F2 generations (BSA-seq) was correlated with a disease resistance interval containing 15 genes. Then, using bioinformatics analysis and differential expression analysis, five candidate genes were identified: Glyma.02G211400, Glyma.18G252800, Glyma.18G285800, Glyma.18G287400 and Glyma.18G298200. Our results provides a key basis for analyzing the soybean resistance mechanism against soybean cyst nematode and cloning soybean resistance genes.